Antibacterial Activity of n-Hexane Extract of Jengkol (Archidendron pauciflorum) Peel Against Escherichia coli - Siregar, Juni Yanti Peronika; Fitri, Nurya Syah; Wijiyaningsih, Dinda (CV. Nusantara Scientific Medical, 2025)
Jengkol peel (Archidendron pauciflorum) is a plant with medicinal potential, as it contains bioactive compounds such as saponins, tannins, and flavonoids known to inhibit bacterial growth. Escherichia coli is a Gram-negative bacterium commonly associated with gastrointestinal tract infections. This study aimed to evaluate the antibacterial potential of n-hexane extract of jengkol peel against Escherichia coli. The antibacterial activity was assessed using the disc diffusion method by measuring the diameter of inhibition zones formed around the paper discs. The results demonstrated that the inhibition zone at a concentration of 500 ppm had a diameter of 15.47 mm (Strong category). These findings confirm that n-hexane extract of jengkol peel (Archidendron pauciflorum) possesses the ability to inhibit the growth of Escherichia coli.